Factors Affecting the Students’ Scholastic Performance: A Survey Study - Stephen Karl F. Briones; Rezel Joy R Dagamac; Jayson D. David; Cherry Ann B. Landerio (Indonesian Journal of Educational Research and Technology, 2022)
Academic achievement is one of the essential elements that businesses examine when employing new graduates. This problem calls for intensive survey investigation to find out the Factors Affecting the Academic Performance of Grade 11 students at SKSU-Laboratory High School. This research was conducted to identify the factors affecting the academic performance of students at SKSU-Laboratory High School, which would help provide suggestions that would promote better academic performance that would interest the students in the study area. This study used a questionnaire for quantitative research instruments and has also used a customized method such as an online survey for the study. This study was conducted to explore the different factors that affect students’ academic performance. This study states that the students' environment has excellent effects, enhancing or weakening their academic performance. There are various factors inside and outside school that contribute to the quality of academic performance of students, such as, Parenting Style, Characteristics of the Students, Level of Internet Effectiveness, Teachers Effectiveness, Lack of Motivation, and Students Career Choice are the factors that affect students’ academic performance.